Intercellular Mitochondrial transfer: Therapeutic implications for energy metabolism in heart failure - Huan He; Weiwei Huang; Zigang Pan; Lingjun Wang; Zhongqi Yang; Zixin Chen (Pharmacological Research)
Heart failure (HF) remains one of the leading causes of high morbidity and mortality globally. Impaired cardiac energy metabolism plays a critical role in the pathological progression of HF. Various forms of HF exhibit marked differences in energy metabolism, particularly in mitochondrial function and substrate utilization. Recent studies have increasingly highlighted that improving energy metabolism in HF patients as a crucial treatment strategy. Mitochondrial transfer is emerging as a promising and precisely regulated therapeutic strategy for treating metabolic disorders. This paper specifically reviews the characteristics of mitochondrial energy metabolism across different types of HF and explores the modes and mechanisms of mitochondrial transfer between different cell types in the heart, such as cardiomyocytes, fibroblasts, and immune cells. We focused on the therapeutic potential of intercellular mitochondrial transfer in improving energy metabolism disorders in HF. We also discuss the role of signal transduction in mitochondrial transfer, highlighting that mitochondria not only function as energy factories but also play crucial roles in intercellular communication, metabolic regulation, and tissue repair. This study provides new insights into improving energy metabolism in heart failure patients and proposes promising new therapeutic strategies.